2020
DOI: 10.1016/j.futures.2020.102640
|View full text |Cite
|
Sign up to set email alerts
|

Can robots tackle late-life loneliness? Scanning of future opportunities and challenges in assisted living facilities

Abstract: Highlights Social robots entail opportunities and challenges in decreasing emotional and social loneliness. A futures scanning was conducted on technology for older people in assisted living (AL). The analytical frame was built on Robert Weiss’ division of relational functions, and on a distinction between direct and indirect social robots. Social robots could tackle both emotional and social loneliness by empowering people. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…This risk was reported by family members (26) as well as OAs (45). Several works have discussed how this kind of technology-based care-related interventions should promote and enhance human contact rather than threaten it (60)(61)(62). Regarding this issue, a solution suggested is that professionals who administer video calls activities monitor the balance between the modalities of social contact that are offered to older adults in an institution.…”
Section: Ethical Questionsmentioning
confidence: 99%
“…This risk was reported by family members (26) as well as OAs (45). Several works have discussed how this kind of technology-based care-related interventions should promote and enhance human contact rather than threaten it (60)(61)(62). Regarding this issue, a solution suggested is that professionals who administer video calls activities monitor the balance between the modalities of social contact that are offered to older adults in an institution.…”
Section: Ethical Questionsmentioning
confidence: 99%
“…Robots can be deployed for disinfection of the COVID-19 wards, delivering medications and food to the patients, and remotely measuring patients' vital signs. Additionally, there has been a recent interest in using "social robots" to deal with the loneliness faced by older people in assisted living (Pirhonen et al, 2020). As per a survey conducted by Healthwatch North Sommerset, 63% of elderly and vulnerable people felt isolated and lonely due to the lockdown, with the majority saying this affected their wellbeing and physical health (Angear, 2020).…”
Section: Roboticsmentioning
confidence: 99%
“…Pirhonen et al ( 25 ) conducted a study on the impact of social robots and communicating technology in decreasing social and emotional loneliness in elderly residents. Assessed aspects were those included in the analytical frame built on Robert Weiss' division of relational functions: Social integration, attachment, reassurance of worth, opportunity for nurturance, guidance in stressful situations, and sense of reliable alliance.…”
Section: Autonomous Robotic Applications For Patients With Advanced Dementiamentioning
confidence: 99%
“…The authors identified that social robots can positively influence both social and emotional loneliness in this population. However, ethical concerns related to lack of human contact and deception still need to be considered before using social robots when caring for the elderly ( 25 ).…”
Section: Autonomous Robotic Applications For Patients With Advanced Dementiamentioning
confidence: 99%